KARAKTERISTIK KIMIA DAN ORGANOLPETIK PEMPEK LENJER KECIL KERING DENGAN PERLAKUAN KONSENTRASI CaCl2 - Alhanannasir Alhanannasir; Asep Dodo Murtado (Faculty of Agricultural Technology, University of Jember, 2020)
As an authentic food of Palembang people in South Sumatera Province, pempek is famous local food caused of unique color (yellowish-white color), flavor (fishy flavor), and chewy texture. Pempek as semi-wet food that can be dried to decrease water content and increase the shelf life. Dried pempek has a lighter and smaller volume material and making it easier to distribute and expand marketing. Pempek can be prepared from ground fish (cork fish), tapioca flour, salt, and water. These ingredients are mixed to form a dough. Pempek dough can be formed into a small pempek, such as lenjer, pastel, otak-otak, adaan, keriting, and kapal selam. Pempek is generally has a wet form. Wet pempek has a high water content of 50-60%, so it had shelf life about 3-4 days. Therefore, wet pempek must be dried to make it long shelf life. The aim of the research was to know about small dried pempek lenjer characteristic based on various addition of CaCl2. The treatment of various CaCl2 concentrations has a very significant effect on water content and protein content (chemical value) and significantly influence the organoleptic properties (aroma, color, and taste) of the dried pempek lenjer. The 1.5% concentration of CaCl2 (C3) treatment has the highest average level of likeness on aroma 3.75, color 3.90, and taste 3.95 with preferred criteria on a dried pempek lenjer. Keywords: chemical, organoleptic, small dried pempek lenjer